Cross-validation of the 20- versus 30-s Wingate anaerobic test - Laurent, C. M.; Meyer, M. C.; Robinson, C. A.; Green, J. M. (European Journal of Applied Physiology, 2007)
The 30-s Wingate anaerobic test (30-WAT) is the most widely accepted protocol for measuring anaerobic response, despite documented physical side effects. Abbreviation of the 30-WAT without loss of data could enhance subject compliance while maintaining test applicability. The intent of this study was to quantify the validity of the 20-s Wingate anaerobic test (20-WAT) versus the traditional 30-WAT. Fifty males (mean ± SEM; age = 20.5 ± 0.3 years; Ht = 1.6 ± 0.01 m; Wt = 75.5 ± 2.6 kg) were randomly selected to either a validation (N = 35) or cross-validation group (N = 15) and completed a 20-WAT and 30-WAT in double blind, random order on separate days to determine peak power (PP; W kg-1), mean power (MP; W kg-1), and fatigue index (FI; %). Utilizing power outputs (relative to body mass) recorded during each second of both protocols, a non-linear regression equation (Y 20WAT+10 = 31.4697 e-0.5[ln(X second/1174.3961)/2.63692]; r 2 = 0.97; SEE = 0.56 W kg-1) successfully predicted (error ~10%) the final 10 s of power outputs in the cross-validation population. There were no significant differences between MP and FI between the 20-WAT that included the predicted 10 s of power outputs (20-WAT+10) and the 30-WAT. When derived data were subjected to Bland-Altman analyses, the majority of plots (93%) fell within the limits of agreement (±2SD). Therefore, when compared to the 30-WAT, the 20-WAT may be considered a valid alternative when used with the predictive non-linear regression equation to derive the final power output values.